A Fiqh Muamalah Analysis of Contractual Practices in the E-Bekal Payment System at Nurul Jadid Islamic Boarding School - Hurriyatus Sa’idah; Nurul Huda (Indonesian Journal Economic Review (IJER), 2026)
This study examines the implementation of contracts within the E-Bekal digital payment system used by students at Nurul Jadid Islamic Boarding School from the perspective of fiqh muamalah. The rapid development of Sharia-based financial technology in Islamic boarding schools has encouraged the adoption of cashless payment systems; however, previous studies have predominantly focused on digitalization effectiveness, consumer behavior, and financial management, while limited attention has been given to the analysis of multi-contract practices embedded in pesantren-based digital payment systems. This research therefore addresses the gap by specifically analyzing the integration of wadi’ah, bai’, and wakalah contracts within the E-Bekal platform. This study employs a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and documentation involving system administrators, cooperative officials, student guardians, and student users. The findings reveal that the operational mechanism of E-Bekal consists of balance top-ups by guardians, digital fund storage, and payment transactions within the pesantren business units. These practices reflect the application of wadi’ah in the deposit and storage of funds, bai’ in purchasing transactions, and wakalah in the management of the payment system. The study further finds that the integration of these contracts forms a Sharia-compliant digital financial ecosystem that promotes transparency, financial control, and transaction efficiency while remaining free from elements of riba and gharar. The novelty of this study lies in its comprehensive fiqh muamalah analysis of a pesantren-based digital payment ecosystem through a multi-contract approach. Academically, this study contributes to the development of Sharia fintech discourse, particularly regarding the adaptation of Islamic commercial law within contemporary digital payment systems in Islamic educational institutions.